SARS-CoV-2 virus: origin, structure and replication cycle - Katarzyna Kuczyńska; Jolanta Barbara Zawilska; Julia Badura; Bartłomiej Strehl (Polish Pharmaceutical Society, 2021)
In December 2019, a novel highly pathogenic coronavirus SARS-CoV-2, which can be transmitted from person to person, was discovered in patients with infectious respiratory disease in Wuhan, Hubei Province, China. The disease, now known as the 2019 coronavirus disease (COVID-19), has spread rapidly around the world causing a pandemic. This survey presents basic information on the structure and replication cycle of SARS-CoV-2. Fundamental discoveries in the genetics and molecular biology of the virus paved the way to design and development of molecules that would act as potential therapeutic agents for COVID-19.The virus belongs to the β-coronavirus 2B lineage. Comparison of the SARS-CoV-2 genome sequence and other available β-coronavirus genomes suggests that it may have evolved naturally from the RaTG13 bat strain of coronaviruses. The virus has a positive-sense single-stranded RNA that acts as mRNA following cellular entry and is completely dependent on the translation machinery of the host cell. The genomic RNA of SARS-CoV-2 comprises 14 open reading frames (ORFs). Two main ORFs, ORF1a and ORF1b, encompasses two-thirds of the genome and are translated to polyproteins pp1a and pp1ab, respectively. These polyproteins are processed by viral proteases (papain-like protease and chymotrypsin-like protease), to produce 16 nonstructural proteins (Nsp). The remaining one-third of the genome encodes four major structural proteins: spike (S), membrane (M), envelope (E) and nucleocapsid (N), and seven accessory proteins. SARS-CoV-2 infects human cells by binding to its receptor, i.e. angiotensin converting enzyme 2 (ACE2) at the cell surface through the receptor binding domain of its S protein. Following the entry into the host cell, the genetic material is released into the cytoplasm, and the synthesis of viral proteins necessary for the further process of replication and translation takes place. After mature virus particles are formed, they travel in Golgi vesicles to the host cell membrane where they are released into extracellular space by exocytosis. With the continued spread of SARS‐CoV‐2 around the world, thousands of mutations have been identified, some of which have relatively high incidences. The following proteins exhibited the highest mutation density: N, S, Nsp2, Nsp3, Nsp5, Nsp6, Nsp7, Nsp12, Nsp13, Orf3 and Orf8. The changes in SARS‐CoV‐2 proteins caused by mutations can not only affect virus transmission, pathogenesis, and immunogenicity, but also give rise to false negative diagnoses and drug resistance.